Late Acheulian stone-working by the riverbank: Patterns of continuity and change reflected in Jaljulia lithic assemblages, Israel - Tamar Rosenberg-Yefet; Aviad Agam; Ella Assaf; Bar Efrati; Yafit Kedar; Vlad Litov; Maayan Shemer; Ran Barkai (PLoS ONE, 2025)
The Lower Paleolithic Late Acheulian marks an exceptional phase in human cultural evolution, encompassing notable transformations and innovations across Africa and Western Eurasia alongside the persistence of well-practiced Acheulian modes of adaptation. Lithic transformations mentioned here include innovative stone-working technologies such as prepared cores, Quina-like scrapers and possible origin of systematic blade production. These innovations provide a glance into potential changes in technological organization of lithic production that might reflect innovative modes of adaptation oriented towards changes in economy, environment and world-views of these early hominin groups. The open-air, Late Acheulian site of Jaljulia makes a significant contribution to the study of this transformative phase at the very end of the long Acheulian tradition in the Levant. The site was excavated to a relatively large extent (ca. 80m 2 ) and the excavation yielded rich lithic assemblages of typical Late Acheulian technological components from several localities, dated to ca. 500–3/200 ka. The lithic assemblages are mostly dominated by flake-production, flake-tools, and numerous Handaxes. This paper presents the comprehensive analyses of the flint assemblages from five Jaljulia localities (Localities A–E). The results presented and discussed here are intriguing, as all five assemblages encompass components that could be regarded as forbearers of post-Acheulian industries. The use of prepared cores might signal an early appearance of the Middle Paleolithic Levallois concepts, and in order to stress this point, these cores are termed here “proto-Levallois”. Quina-like scrapers and blades are prominent, possibly reflecting the early adoption of technologies that became more common in the post-Acheulian, Acheuleo-Yabrudian cultural complex of the Levant. Based on this remarkable lithic repertoire, this paper discusses possible patterns of continuity and change in lithic production from the Late Acheulian to later industries and suggests refinements to the reduction trajectories variability.